2014
DOI: 10.3233/jad-132489
|View full text |Cite
|
Sign up to set email alerts
|

Qualification of a Surrogate Matrix-Based Absolute Quantification Method for Amyloid-β42 in Human Cerebrospinal Fluid Using 2D UPLC-Tandem Mass Spectrometry

Abstract: The primary aims of this work were to: 1) establish a calibrator surrogate matrix for quantification of amyloid-β (Aβ)42 in human cerebrospinal fluid (CSF) and preparation of quality control samples for LC-MS-MS methodology, 2) validate analytical performance of the assay, and 3) evaluate its diagnostic utility and compare it with the AlzBio3 immunoassay. The analytical methodology was based on a 2D-UPLC-MS-MS platform. Sample pretreatment used 5 M guanidine hydrochloride and extraction on μElution SPE columns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
93
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(102 citation statements)
references
References 37 publications
4
93
0
5
Order By: Relevance
“…If the methods give correlating results, the use of a commutable CRM for calibration should make it possible to produce values that are comparable irrespective of analytical method, time or place of measurement [32]. In the present study, it was shown that the majority of the results of the different immunoassays correlate well; and in addition, they also correlate with results from the SRM-based method, which has now been published as candidate SRM-based RMP [27,33]. The first substudy confirmed that the majority of methods tested were highly correlated (R 2 > 0.9) as shown previously [19].…”
Section: Discussionmentioning
confidence: 49%
“…If the methods give correlating results, the use of a commutable CRM for calibration should make it possible to produce values that are comparable irrespective of analytical method, time or place of measurement [32]. In the present study, it was shown that the majority of the results of the different immunoassays correlate well; and in addition, they also correlate with results from the SRM-based method, which has now been published as candidate SRM-based RMP [27,33]. The first substudy confirmed that the majority of methods tested were highly correlated (R 2 > 0.9) as shown previously [19].…”
Section: Discussionmentioning
confidence: 49%
“…Immunodetection approaches are straightforward, but they present some drawbacks such as difficulties to develop good multiplex panels, to detect additional forms of Aβ peptides, or to reach a low variability from batch to batch, and between providers. MS could help resolve these issues with the development of LC-MS/ MS reference methods [55,56] along with the forthcoming availability of a CRM. In addition, MS will be useful to qualify, control and improve comparability of results from existing immunoassays by providing calibrators with target values traceable to a reference method and/or CRM.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, candidate reference methods [reference measurement procedure (RMP)] have been proposed for the absolute quantification of Aβ 1-42 by LC-MS/MS [55,56]. If selected as higher order reference method, they could be used to certify a reference material [certified reference material (CRM)] that would become the "gold standard" with which all in vitro diagnostic kits should be calibrated with to fulfill requirements of the European Commission in vitro diagnostic device directive (IVD Directive 98/79/ EC) [57].…”
Section: Immuno-precipitation-liquid Chromatography-ms (Ip-lc-ms/ms) mentioning
confidence: 99%
See 1 more Smart Citation
“…In 2014, a candidate mass spectrometry-based reference method for Aβ 1-42 and a surrogate matrix for calibrators and quality control samples were developed under the auspices of the Global Biomarkers Standardization Consortium [10]. This represents important progress toward the qualification of CSF biomarkers because it provides, by direct measure of an analyte, a reproducible reference method against which the various immunoassay platforms can be compared.…”
Section: Ad Biomarkers -Csf and Imagingmentioning
confidence: 99%